2016
DOI: 10.3389/fnbeh.2016.00221
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the Pair Bond: Neural and Hormonal Effects of Separation and Reunion in a Monogamous Primate

Abstract: Social monogamy at its most basic is a group structure in which two adults form a unit and share a territory. However, many socially monogamous pairs display attachment relationships known as pair bonds, in which there is a mutual preference for the partner and distress upon separation. The neural and hormonal basis of this response to separation from the adult pair mate is under-studied. In this project, we examined this response in male titi monkeys (Callicebus cupreus), a socially monogamous New World prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 84 publications
1
37
0
Order By: Relevance
“…We found that OT treatments had more prominent effects following a long-separation challenge that was designed to induce biobehavioral distress (Cavanaugh et al, 2016) than following a short-separation challenge that was designed to be minimally stressful (Mustoe et al, 2015, 2016). In male titi monkeys ( Callicebus cupreus ), levels of CSF OT were elevated during both prolonged (48 hr) and long-term (2–3 weeks) separation from a pairmate (Hinde et al, 2016). While CSF OT levels remained elevated during reunion with their pairmate and during exposure to opposite-sex strangers, following separation, reunion with their pairmate stimulated coordinated release of both central and peripheral OT.…”
Section: | General Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that OT treatments had more prominent effects following a long-separation challenge that was designed to induce biobehavioral distress (Cavanaugh et al, 2016) than following a short-separation challenge that was designed to be minimally stressful (Mustoe et al, 2015, 2016). In male titi monkeys ( Callicebus cupreus ), levels of CSF OT were elevated during both prolonged (48 hr) and long-term (2–3 weeks) separation from a pairmate (Hinde et al, 2016). While CSF OT levels remained elevated during reunion with their pairmate and during exposure to opposite-sex strangers, following separation, reunion with their pairmate stimulated coordinated release of both central and peripheral OT.…”
Section: | General Discussionmentioning
confidence: 99%
“…While CSF OT levels remained elevated during reunion with their pairmate and during exposure to opposite-sex strangers, following separation, reunion with their pairmate stimulated coordinated release of both central and peripheral OT. Moreover, males that previously reproduced with their pairmate had lower neural activity in the supraoptic (SON) and paraventricular (PVN) nuclei of the hypothalamus (central hubs of OT production) during exposure to an opposite-sex stranger, than males that had not reproduced with their pairmate (Hinde et al, 2016). This suggests that oxytocinergic activity underlies reunion behavior differently as a function of experiences in the pair (i.e., raising vs. not raising offspring), and that the OT system is sensitive to the level of reproductive success of an individual’s current relationship and implicates fatherhood as bond-enhancing experience.…”
Section: | General Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects, pair mates and young offspring (less than one year old) were relocated to a metabolism room 48 hours prior to their positron emission tomography (PET) scan. As in our previous PET studies (Bales et al, 2007; Hinde et al, 2016; Maninger et al, 2017), animals were relocated prior to the scan in order to reduce the possible effect of novel housing on brain metabolism. Animals were fasted 6–12 h prior to the scan, with water available throughout the pre-scan period.…”
Section: Methodsmentioning
confidence: 99%